FT IR and Laser Raman Spectroscopic Investigation of Transition Metal Halide Complexes of Benzidine - Bulat, Taner; Özel, Ayşen E.; Başar, Gönül; AKYÜZ, SEVİM (Elsevier, 1997)
FT-IR and Raman spectra of MX2Bzn {where M=Mn or Co, X=Cl; M=Cd, X=Cl or I; and Bzn=benzidine; C12H8(NH2)2} complexes have been investigated in the region between 200–4000 cm−1 and all the bands observed are assigned. Spectroscopic investigation indicates that benzidine molecules are bound to metal through both nitrogen lone pairs and bidentate ligands. It is found that benzidine molecules are centrosymmetric in the complexes. Coordination effects on internal modes of benzidine, particularly on the NH2 group vibrations are discussed. The general influence of the metal on the state of the coordinated amino-group is found to be similar to the characteristics of the aniline complexes.
Keywords: Transition metal complexes; Benzidine complexes; Raman Spectroscopy